Resesi Ekonomi dan Implikasinya dari Perspektif Hukum Bisnis (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2021)
The period of the Covid-19 pandemic has given rise to prolonged multi-sector problems, including the economic sector, which then resulted in an economic recession and its implications. This condition is undoubtedly expected not to occur in a long time. The hope of all parties, including the government that the recession will return to normal soon by trying various steps and approaches such as the business law approach. This paper focuses on studying how to capture an economic recession and its implications from a business law perspective as an alternative to economic recovery. This research is a library research by tracing bibliographic texts related to economic recession, focusing on the business law approach. The research finding is that the law can provide procedural solutions in resolving economic recessions from business law. Law can create a balance (balance) because it is related to economic development initiatives. The law also plays a role in determining the definition and clear status (definition and clarity of status). In the end, the law must also provide a clear definition and status regarding the consequences of social interaction and accommodate (accommodation) a balance clearly for the interests of individuals or groups in society.